The Utilisation of Synchronous and Asynchronous Online Learning Media in Distance Learning in Madrasah Aliyah - Hakim, Arif Rahman; Wibowo, Arif (IAIN Ponorogo, 2023)
The use of online learning media, both synchronous and asynchronous, has become part of an interesting phenomenon and deserves attention in today's era of technological development. This study aims to analyse the use of online media in distance learning in Madrasah Aliyah in terms of media utilisation, namely, the aspect of determining media and the aspect of media implementation. This research used descriptive qualitative methods in Madrasah Aliyah Negeri in Ponorogo. Data collection techniques consist of interviews, observation and documentation. The data is analysed using the Miles Huberman model of data reduction, display, and verification. The results of this study are as follows. First, the determination of synchronous and asynchronous online media in the implementation of distance learning in Madrasah Aliyah is carried out through three main points sequentially, namely setting criteria, determining alternative media, and performance in the classroom. Second, the implementation of synchronous and asynchronous online media in the implementation of distance learning in Madrasah Aliyah is carried out in two forms, individually and in combination. Synchronous online media is implemented in virtual face-to-face activities and material deepening. In contrast, asynchronous online media is implemented in practical exercises and assignments. As for presentations, discussions and exams of synchronous and asynchronous online media are implemented combatively.